O ensino de ciências por investigação : uma abordagem para elevar os níveis de letramento científico nos anos finais do ensino fundamental - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
Scientific Literacy (SL) refers to an individual's ability to act critically in society on matters relating to science and its conceptions, while also understanding the world around them. However, large-scale assessments and small-scale national studies point to a low level of SL in the country. The national and state curricula for science teaching have developed skills and competencies that involve students' CL from the early years onwards, and have proposed investigative practices as effective in achieving this goal. In addition to curricula, studies and research into new teaching approaches show that inquiry-based science teaching can promote students' CL. With this in mind, this study aims to measure the level of CL in a 9th grade class at a state school in the city of Anápolis-GO, by constructing a Diagnostic Instrument for Levels of Scientific Literacy (IDiNLC). After analyzing the results of the IDiNLC, an intervention was carried out by applying four Investigative Teaching Sequences (SEI) during the 2022 school term, based on the Curriculum Document for Goiás (DC-GO). At the end of the teaching sequences, the students answered a new questionnaire, making it possible to check whether the Investigative Science Teaching approach, through the use of SEIs, contributed to increasing the students' Scientific Literacy Level. The analysis of the initial IDiNLC made it possible to conclude that most of the students in the sample class have Scientific Literacy below Level 1. The observations related to the open-ended items also highlight the deficiencies in writing and argumentation. The final IDiNLC revealed the effectiveness of inquiry teaching in improving the students' NLC. It should also be noted that CL is a process and that knowing how to diagnose the CL of the students and the class makes it easier to plan tasks and assessments that are consistent with the students' cognitive abilities.
Teaching science through research : an approach to raise scientific literacy levels in the final years of elementary school
Keywords: Ensino de Ciências; Sequências de Ensino Investigativas; Instrumento diagnóstico.; Science Teaching; Investigative Teaching Sequences; Diagnostic Instrument.; EDUCACAO::ENSINO-APRENDIZAGEM